The Effects of Transformational Leadership Style Toward Employee Performance With Organizational Culture As Mediating Varible in BPJS Kesehatan Pontianak - Khair, Darul B12112022 (Jurnal Manajemen Update, 2018)
This study aims to assess the performance of Pontianak Health BPJS employees by using transformational leadership style variables as independent variables and organizational culture as mediating variables. Data collection method using questionnaires which are distributed to 53 respondents, using census sampling techniques and Likert scales is used for data measurement. The Classical Assumption Test and path analysis were used to process the data using the IBM SPSS v22 application. The results of this study indicate that transformational leadership style has a positive and significant effect on employee performance, transformational leadership style has a positive and significant relationship with organizational culture, and organizational culture has a positive but not significant impact on employee performance.Keywords : Transformational Leadership Style, Organizational Culture, Employee Performance, BPJS Keesehatan Pontianak